Formal Methods for Open Object-Based Distributed Systems 10th IFIP WG 6.1 International Conference, FMOODS 2008, Oslo, Norway, June 4-6, 2008 Proceedings - Barthe, Gilles (Programming and Software Engineering,, 2008)
This book constitutes the refereed proceedings of the 10th IFIP WG 6.1 International Conference on Formal Methods for Open Object-Based Distributed Systems, FMOODS 2008, held in Oslo, Norway, in June 2008. The 14 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from 35 submissions. The papers cover topcics such as semantics of object-oriented programming; formal techniques for specification, analysis, and refinement; model checking; theorem proving and deductive verification; type systems and behavioral typing; formal methods for service-oriented computing; integration of quality of service requirements into formal models; formal approaches to component-based design; and applications of formal methods.